To Evaluate and Compare the Position of Frankfort Horizontal Plane and Camper's Plane to Occlusal Plane: An In Vivo Study - Asusa C Loli; Tarun Kalra; Manjit Kumar; Ajay Bansal; Abhishek Avasthi (Dental Journal of Advance Studies)
Aim: This study was undertaken to evaluate and compare the position of Frankfort horizontal plane and Camper's plane to the occlusal plane. Materials and methods: In this study, 80 subjects aged between 19 and 25 years with normal occlusion were selected from undergraduate and postgraduate students of Bhojia Dental College and Hospital, Baddi, Himachal Pradesh, India. Measurement of the clinical parameters was done using computer software program Screen Protractor version 4.0 and the radiographic (lateral cephalograms) were traced using an X-ray viewer. Results: It was observed that neither the clinical nor the radiographic (lateral cephalogram) Camper's plane was parallel to the occlusal plane but on comparison it was found that clinical Camper's plane was almost parallel to the occlusal plane. Conclusion: The study showed that neither the Camper's plane nor the Frankfort horizontal plane was parallel to occlusal plane.